Accessibility Assessment of Prehospital Emergency Medical Services considering Supply-Demand Differences - Zhaoqing Shen; Ge Gao; Zhen Wang (Journal of Advanced Transportation)
The reasonable accessibility assessment method is an important basis for the measurement of the level of prehospital emergency medical services. There is no general model for prehospital emergency care in traditional accessibility evaluation, and its supply-demand characteristics have also been ignored. Based on the three-step floating catchment area (3SFCA) model, the supply-demand three-step floating catchment area (SD3SFCA) model is proposed in this paper, which can express the difference between supply and demand of prehospital emergency medical services and accurately simulate unified dispatching of emergency centers. The unified dispatching behavior of emergency centers is simulated based on the potential service capacity of emergency stations with a supply-demand difference. The supply capacity of different emergency facilities is quantified from the perspective of infrastructure and technical quality. The needs of typical population densities are taken into account and adjusted by the weighting index. The validity of the model is verified, with the prehospital emergency medical service in the West Coast New District of Qingdao as an example. The results show that the model can effectively measure the accessibility level of prehospital emergency services and truly reflect the characteristics of supply and demand. Compared with previous models, the model has been significantly improved, which can provide an important reference for optimizing the allocation of prehospital emergency resources.